2012
DOI: 10.1021/bi3000879
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Oxidase Functions as a Superoxide Generating NADH Oxidase: An Important Redox Regulated Pathway of Cellular Oxygen Radical Formation

Abstract: The enzyme aldehyde oxidase (AO) is a member of the molybdenum hydroxylase family that includes xanthine oxidoreductase (XOR); however, its physiological substrates and functions remain unclear. Moreover, little is known about its role in cellular redox stress. Utilizing electron paramagnetic resonance spin trapping we measured the role of AO in the generation of reactive oxygen species (ROS) through the oxidation of NADH, and the effects of inhibitors of AO on NADH-mediated superoxide ( O2•−) generation. NADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 59 publications
2
62
1
Order By: Relevance
“…While complex I harbors a noncovalently FMN as a mediator for electron transport between NADH and the [2Fe-2S] cluster, Na ϩ -NQR contains an FAD for NADH oxidation, with a [2Fe-2S] center in close proximity (3). Thus, as reported for complex I and aldehyde oxidase (55), one-and two-electron-reduced FAD may act as an electron donor for superoxide formation in the Na ϩ -NQR. In this case, cytoplasmic superoxide formation would mainly depend on NADH oxidation activity catalyzed by FAD in the cytoplasmic domain of subunit NqrF (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…While complex I harbors a noncovalently FMN as a mediator for electron transport between NADH and the [2Fe-2S] cluster, Na ϩ -NQR contains an FAD for NADH oxidation, with a [2Fe-2S] center in close proximity (3). Thus, as reported for complex I and aldehyde oxidase (55), one-and two-electron-reduced FAD may act as an electron donor for superoxide formation in the Na ϩ -NQR. In this case, cytoplasmic superoxide formation would mainly depend on NADH oxidation activity catalyzed by FAD in the cytoplasmic domain of subunit NqrF (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…A similar mechanism was described for inhibition of cytochrome P450 reductase (Tew, 1993), and numerous papers published in the past two decades indicate that DPI is a nonselective inhibitor of NAD(P)H-dependent enzymes using flavins as redox cofactors (Aldieri et al, 2008). These include NO synthases, mitochondrial complex I, cytochrome P450 reductase, xanthine oxidase, and, described recently, the related molybdo-flavoprotein aldehyde oxidase (Kundu et al, 2012). The affinity constants found in the literature vary from 50 nM to 2.8 mM, with IC 50 values in the range of 0.3-5.6 mM for inhibition of NADPH oxidase (Aldieri et al, 2008).…”
Section: Introductionmentioning
confidence: 66%
“…In addition to flavin prosthetic groups, metal-bound porphyrins were identified as targets of aryliodonium compounds, suggesting that modification of flavocytochrome b may contribute to NADPH oxidase inhibition (Doussiere et al, 1999). Mechanism-based modification of flavin or heme prosthetic groups explains inhibition by DPI of a wide variety of flavoproteins, including NADH:ubiquinone oxidoreductase, NO synthases, xanthine oxidase, cytochrome P450 reductase (see Aldieri et al, 2008, for review), and aldehyde oxidase (Kundu et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ibdah et al (2009), in their AAO4 activity assay, employed NAD + as a cosubstrate together with the aldehyde substrate. However, the use of NAD + by plants, or for that matter by any eukaryotic AO, is not known (Nishino and Nishino, 1989;Terao et al, 1998;Garattini et al, 2009;Kundu et al, 2012;Zarepour et al, 2012;Li et al, 2014). Moreover, Coelho et al (2012) recently demonstrated that the lack of residues leading to a flexible loop around the FAD domain in mammalian AO crystal structure can account for the fact that AOs are pure oxidases and cannot use NAD + as the final acceptor of reducing equivalents.…”
Section: The Response Of Aao4 Siliques To Various Kinds Of Aldehydesmentioning
confidence: 99%